Clinical characteristics of pediatric patients hospitalized with community-acquired pneumonia and cytomegalovirus DNA detected in bronchoalveolar lavage fluid - Wang, Xinyu; Lu, Yanhong; Chen, Feng; Ruan, Linan; Gu, Lingtong; Wang, Ting; Dong, Heting; Wang, Yuqing; Hao, Chuangli; Huang, Li; Yan, Yongdong; Sun, Huiming; et al. (Frontiers in Pediatrics, 2024)
Background: This study aimed to investigate the clinical characteristics of pediatric patients hospitalized with community-acquired pneumonia (CAP) and concomitant cytomegalovirus (CMV) infection.This cross-sectional study enrolled consecutive pediatric patients admitted with CAP who tested positive for CMV DNA in bronchoalveolar lavage fluid (BALF).Flexible fiberoptic bronchoscopy was performed when routine treatment for CAP proved ineffective. The study participants were further stratified into two groups based on CMV serological test results: recent CMV infection group and CMV replication group. Clinical characteristics were compared between these two groups.Results: Among 124 patients aged 1-11 months included in this study, 80 (64.5%) patients were categorized as having recent CMV infection, and 44 (35.5%) tested positive for CMV replication. Co-infection with other pathogens was detected more frequently in the CMV replication group (n=29, 65.9%) than in the recent CMV infection group (n=35, 43.7%; P=0.018). Patients with recent CMV infection were younger and exhibited higher levels of alanine transaminase (ALT) and aspartate aminotransferase compared to those with CMV replication (all P<0.05). Multivariable regression analysis showed age was independently associated with recent CMV infection (odds ratio [OR], 0.707; 95% confidence interval [CI], 0.586-0.853; P<0.001).Notably, receiver operating characteristic curve analysis showed that a CMV PCR level of 3840 copies/mL in blood samples had a sensitivity of 34.7% and specificity of 90.0% for diagnosis of recent CMV infection with an area under the curve (AUC) of 0.625 (95% CI: 0.513-0.736, P=0.048). A CMV PCR level of 6375 copies/mL in urine samples had a sensitivity of 77.1% and specificity of 61.5% for diagnosis of recent CMV infection with an AUC of 0.695 (95% CI: 0.531-0.858, P=0.04). Furthermore, multivariate linear regression analysis revealed that the blood CMV DNA copy number was associated with ALT (B=0.001; P<0.001).The CMV DNA copy numbers in blood and urine could serve as discriminatory markers between recent CMV infection and CMV replication.Measuring CMV DNA levels in blood may be an effective method for monitoring liver function impairment in pediatric patients presenting with CAP and concurrent CMV infection.